The Control of Hyperglycemia in Alloxan Treated Diabetic Mice through the Stimulation of Hepatic Insulin Synthesis due to the Production of Nitric Oxide - Ghosh, R.; Jana, P.; Sinha, A. K. (Experimental and Clinical Endocrinology & Diabetes, 2012)
The hepatocytes from the adult mice when stimulated by glucose had been reported to synthesize and secrete insulin. The feasibility of controlling hyperglycemia in alloxan induced diabetic mice through hepatic synthesis of insulin was studied.Insulin synthesis was determined by in vitro translation of mRNA and by immunohistochemistry of the hepatocytes and assayed by enzyme linked immunosorbent assay (ELISA). Dermcidin isoform 2 (dermcidin) was measured by ELISA. Nitric oxide was measured by methemoglobin method. Insulin synthesis was quantitated by immunoblot technique and the expression of proinsulin genes I and II in the hepatocytes was quantitated by cDNA synthesisIt was found that in contrast to normal hepatocytes, the hepatocytes from the diabetic mice showed impaired insulin synthesis in the presence of glucose that was related to the inhibition of nitric oxide synthesis through the synthesis of dermcidin, a potent competitive inhibitor of nitric oxide synthase. The increase of systemic NO synthesis either by oral use of 0.7 mM acetyl salicylic acid (aspirin) or by dermal application of 0.28 mmol sodium nitroprusside in saline soaked in cotton pad was found to decrease blood glucose level from 600 mg/dL to 120 mg/dL with concomitant increase of plasma insulin level from 5 µunits/dL to 38 µunits/dL. And subsequently normalized dermcidin level from 80 nM to 4.5 nM within 24 h (p<0.001; n=10).Our studies suggested the possibility of controlling hyperglycemia in alloxan induced diabetic mice by the stimulation of the hepatic insulin synthesis through the systemic stimulation of NO production in the hepatocytes.
Keywords: insulin; hyperglycemia; dermcidin isoform 2; acetyl salicylic acid; nitric oxide